Refined genotype-phenotype correlations in cases of chromosome 6p deletion syndromes. - Mirza, G; Williams, R; Mohammed, S; Clark, R; Newbury-Ecob, R; Baldinger, S; Flinter, F; Ragoussis, J (2004)
Clinical reports of cases with deletions in chromosome 6p are relatively rare. We present a detailed study by fluorescent in situ hybridisation (FISH) of six new cases with distinct but overlapping 6p deletions involving the 6p24-pter chromosomal segment. Chromosomal breakpoints in individual cases were investigated using a large panel of probes previously mapped and characterised in our laboratory to cover the distal region of 6p. These cases have allowed refinement of genotype-phenotype correlations and strongly suggest a gene involved in regulating the development of hearing is localised within 6p25. There is also evidence for one or more loci involved in heart, skeletal and craniofacial development in the 6p24-p25 region. Furthermore, the Dandy-Walker malformation is associated with deletion of 6p24-pter.